Differences in throwing kinematics among youth baseball pitchers and football quarterbacks - Washington, J.; Gascon, S.; Clardy, K.; Oliver, G. D. (Journal of Athletic Enhancement, 2017)
The purpose of this study was to examine throwing kinematics of youth baseball pitchers and football quarterbacks. Eighteen pitchers (13.6 ± 1.3 years; 169.3 ± 8.0 cm; 62.3 ± 10.2 kg) and fifteen quarterbacks (14.3 ± 1.6 years; 174.9 ± 7.9 cm; 69.1 ± 14.0 kg) participated. Pitchers threw three fastballs to a catcher (46 ft; 14.0 m), while quarterbacks threw three 15 yard (13.7 m) passes to a receiver. Baseball pitchers displayed significantly greater trunk flexion at maximum external rotation (MER), ball release (BR) and maximum internal rotation (MIR) (p<0.001, p=0.003, p=0.007); as well as greater trunk rotation opposite throwing arm side at BR (p=0.048). Football quarterbacks displayed greater trunk rotation to throwing arm side at MER (p=0.002); shoulder horizontal adduction at FC (p=0.004); shoulder external rotation at BR (p=0.036); and elbow flexion at FC and MER (p=0.018, p=0.044). Trunk kinematic differences may be the result of pitchers throwing from a mound versus flat ground, just as upper extremity kinematic differences could be the result of the weight and shape of the ball.